PERAN GELAR PERKARA KHUSUS DALAM PENYELESAIAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA MENGGUNAKAN PENDEKATAN RESTORATIVE JUSTICE DI KEPOLISIAN - Muhammad Reffarm Dwi Putra (2022)
This study aims to determine the role of special cases in the settlement of crimes of domestic violence using a restorative justice approach and the obstacles faced by the police in carrying out special cases in resolving criminal acts of domestic violence using a restorative justice approach. This research is normative research that uses a statute approach and a case approach with data collection techniques in the form of library research and interviews. This study obtained a conclusion, namely 1) making the family more harmonious, making parties aware of the importance of a family unit, socializing the dangers of Domestic Violence and if the case is resolved by legal means; seek information needed to reconcile the two parties and to determine further policing; facilities provided by laws and regulations to litigants if in a case there is an explanation, reopening an investigation based on a pretrial decision, and stopping an investigation in a case that was resolved using a restorative justice approach. 2) One of the parties is absent. rarely do special cases in resolving criminal acts of domestic violence using a restorative justice approach, rules regarding special case titles that are not legally enforceable. Keywords: Special Case Title, Restorative Justice, Domestic Violence